Spatial Variability of Movement, Structure, and Formation of Warm Core Rings in the Northwest Atlantic Slope Sea. Issue 8 (25th August 2022) - Silver, Adrienne; Gangopadhyay, Avijit; Gawarkiewicz, Glen; Andres, Magdalena; Flierl, Glenn; Clark, Jenifer
Abstract: Gulf Stream Warm Core Rings (WCRs) have important influences on the New England Shelf and marine ecosystems. A 10‐year (2011–2020) WCR dataset that tracks weekly WCR locations and surface areas is used here to identify the rings' path and characterize their movement between 55 and 75°W. The WCR dataset reveals a very narrow band between 66 and 71°W along which rings travel almost due west along ∼39°N across isobaths – the "Ring Corridor." Then, west of the corridor, the mean path turns southwestward, paralleling the shelfbreak. The average ring translation speed along the mean path is 5.9 cm s −1 . Long‐lived rings (lifespan >150 days) tend to occupy the region west of the New England Seamount Chain (NESC) whereas short‐lived rings (lifespan <150 days) tend to be more broadly distributed. WCR vertical structures, analyzed using available Argo float profiles indicate that rings that are formed to the west of the NESC have shallower thermoclines than those formed to the east. This tendency may be due to different WCR formation processes that are observed to occur along different sections of the Gulf Stream. WCRs formed to the east of the NESC tend to form from a pinch‐off mechanism incorporating cores of Sargasso Sea water and a perimeter of Gulf Stream water. WCRs that form to the west of the NESC, form from a process called an aneurysm. WCRs formed through aneurysms comprise water mostly from the northern half of the Gulf Stream and are smaller than the classic pinch‐off rings. Plain Language Summary: Warm Core Rings (WCR) are clockwise rotating warm masses of water formed from the Gulf Stream as it flows northeastward off the US east coast into the deep ocean. In this study, a 10‐year WCR tracking dataset was used to analyze the rings' movement through the Slope Sea between 55 and 75°W. Rings tend to follow a narrow path between 66 and 71°W, called the "Ring Corridor." Within this region, there appear to be more long‐lived (lifetime >150 days) rings. Rings that are formed to the west of the New England Seamount Chain are shallower (and smaller), than rings formed to the east of the seamounts. We attribute this difference in ring signatures to different preferred ring formation processes occurring along the Gulf Stream – pinch‐off to the east and aneurysm to the west of the seamounts. The results from this work show important aspects of WCRs that might have been previously overlooked and open up new opportunities for dynamical and numerical simulations and understanding of the behavior of the Gulf Stream system and its rings. Additionally, the WCR tracking data set can play an important role in ecosystem assessment, species stock assessments, and studying cross shelf exchange. Key Points: Within the rings' path (55–75°W), an across‐isobath "Ring Corridor" west of the New England Seamount Chain is identified between 66 and 71°W Rings forming to the west of the New England Seamount Chain have shallower thermoclines and are smaller than rings formed to the east Differences in ring structure and size are attributed to different formation processes: aneurysm and pinch‐off